Cell-Free Supernatant Obtained From a Salt Tolerant Bacillus amyloliquefaciens Strain Enhances Germination and Radicle Length Under NaCl Stressed and Optimal Conditions - Naamala, Judith; Msimbira, Levini A.; Antar, Mohammed; Subramanian, Sowmyalakshmi; Smith, Donald L. (Frontiers in Sustainable Food Systems, 2022)
Seed germination and early plant growth are key stages in plant development that are, susceptible to salinity stress. Plant growth promoting microorganisms (PGPMs) produce substances, in their growth media, that could enhance plant growth under more optimal conditions, and or mitigate abiotic stresses, such as salinity. This study was carried out to elucidate the ability of a NaCl tolerant Bacillus amyloliquefaciens strain's cell-free supernatant to enhance germination and radicle length of corn and soybean, under optimal and NaCl stressed growth conditions. Three NaCl levels (0, 50, and 75 mM) and four cell-free supernatant concentrations (1.0, 0.2, 0.13, and 0.1% v/v) were used to formulate treatments that were used in the study. There were observed variations in the effect of treatments on mean radicle length and mean percentage germination of corn and soybean. Overall, the study showed that Bacillus amyloliquefaciens (BA) EB2003 cell-free supernatant could enhance mean percentage germination and or mean radicle length of corn and soybean. At optimal conditions (0 mM NaCl), 0.2% BA, 0.13% BA, and 0.1% BA concentrations resulted in 36.4, 39.70, and 39.91%, increase in mean radicle length of soybean, respectively. No significant observations were observed in mean radicle length of corn, and mean percentage germination of both corn and soybean. At 50 mM NaCl, 1.0% BA resulted in 48.65% increase in mean percentage germination of soybean, at 24 h. There was no observed effect of the cell-free supernatant on mean radicle length and mean percentage germination, at 72 and 48 h, in soybean. In corn however, at 50 mM NaCl, treatment with 0.2% BA and 0.13% BA enhanced mean radicle length by 23.73 and 37.5%, respectively. The resulting radicle lengths (43.675 and 49.7125 cm) were not significantly different from that of the 0 mM control. There was no observed significant effect of the cell-free supernatant on mean germination percentage of corn, at 50 mM NaCl. At 75 mM NaCl, none of the treatments enhanced mean radicle length or mean percentage germination to levels significantly higher than the 75 mM NaCl. Treatment with 1.0% BA, however, enhanced mean percentage germination to a level not significantly different from that of the 0 mM control, at 72 h. Likewise, in corn, none of the treatments enhanced radicle length to lengths significantly higher than the 75 mM control, although treatment with 1.0% BA, 0.13% BA, and 0.1% BA elongated radicles to lengths not significantly different from the 0 mM NaCl control. Treatment with 0.2% BA, 0.13% BA, and 0.1% BA resulted in mean percentage germination significantly higher than the 75 mM NaCl by 25.3% (in all 3), not significantly different from that of the 0 mM NaCl. In conclusion, concentration of cell-free supernatant and NaCl level influence the effect of Bacillus amyloliquefaciens strain EB2003A cell-free supernatant on mean percentage germination and mean radicle length of corn and soybean.